أثر التحضير الحركي على سرعة رد الفعل لدى لاعبي حائط الصد مركز (3) في الكرة الطائرة - فاضل, رغد; زهرة, ميسم; سعد, غانا (Latakia University Journal -Medical Sciences Series, 2016)
من الصفات التي يجب أن يتمتع بها لاعب حائط الصد في الكرة الطائرة هي سرعة رد الفعل ,والتي تساهم بشكل فعال في قدرة اللاعب على صد الضربات الساحقة للمهاجم المنافس بشكل صحيح , ولكن زمن رد الفعل يتأثر بمدى استفادة اللاعب من المعلومات الأولية (Prime) الموجودة في محيطه للتحضير للحركة القادمة , فعندما يقوم اللاعب بالتحضير الفعال و بشكل مسبق للحركة المطلوبة تتم معالجة هذه المعلومات بشكل أسرع وبالتالي نلاحظ تحسن في زمن رد فعل اللاعب .لذا قمنا بهذه الدراسة لمعرفة تأثير تمارين مصممة خاصة بالتحضير الحركي على سرعة رد الفعل لدى لاعبي حائط الصد مركز (3) في الكرة الطائرة .حيث استخدمنا في هذه الدراسة اختبار ال Priming المقترح من قبل العالمين Rosenbaum and Kormblum , (1982) كاختبار قبلي وبعدي للمجموعتين التجريبية والضابطة لمعرفة أثر تقديم معلومات مسبقة على زمن رد فعل اللاعب . إن المعلومات المقدمة مسبقا إما أن تكون مطابقة للحركة المطلوبة أو حيادية , وقد تم اعتماد طريقة احتساب عدد المحاولات الصحيحة المنفذة من قبل اللاعب للاستدلال على التغيير في سرعة رد الفعل لديه. أظهرت النتائج تحسن في عدد المحاولات الصحيحة للمجموعة التجريبية بعد تطبيق البرنامج التدريبي المقترح في الحالتين( مطابقة - حيادية ) وهنا نستنتج أن البرنامج المطبق قد ساهم في زيادة عدد المحاولات الصحيحة المنفذة مما يدل على زيادة سرعة معالجة المعلومات التي أدت الى تطوير سرعة رد الفعل لدى لاعبي حائط الصد مركز (3). وفي ضوء هذه الاستنتاجات أوصينا بضرورة استخدام البرنامج التدريبي المقترح ضمن الخطط التدريبية الموضوعة لفرق الكرة الطائرة السورية لأهميته في تطوير سرعة رد الفعل التي تعتمد عليها أغلب المهارات الهجومية والدفاعية في هذه اللعبة, وكذلك ضرورة إجراء المزيد من البحوث والدراسات التي تعتمد على الوسائل التدريبية الحديثة .One of the skills that should be possessed by block players in volleyball is reaction speed. It effectively influences the player’s ability to block strong shots from the opponent correctly. However, response time is influenced by how much the player benefits from the prime which is provided around him to prepare for the next movement. When a player effectively prepares for the required movement in advance, these information are processed more rapidly, and thus, we notice an improvement in the player’s reaction time. Thus, we have conducted this study to find out the effect of special exercises designed for motor preparation on reaction speed for block players center (3) in volleyball .For the current study, we have used the priming test, suggested by Rosenbaum and Kormblum (1982) as a prior test and a follow-up test for both test group and blocked group, in order to figure out the effect of providing primes on the player’s reaction time. The primes provided were either identity for the required movementor neutral. We have followed the method of calculating the number of correct attempts executed by the players, in order to infer the change in their reaction speed. The results revealed improvement in the number of correct attempts for test group after applying the suggested training program in the two situations (identity-neutral). Therefore, we find that the applied program has contributed to an increase in the number of correct executed attempts, which suggests an increase in the speed of processing the information, leading to enhancing the reaction speed in block players center (3). In light of these findings, we have recommended the necessity of using the suggested training program as part of the training plans provided for Syrian volleyball teams. This recommendation is due to the program’s importance in improving reaction speed, on which most offensive and defensive skills in this game depends. We have also recommended the necessity of conducting further research and study, based on modern training methods.